Call for roadmap for successful adoption of CSR in Malaysian construction - Zahidy, Anat Anaqie; Sorooshian, Shahryar (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Despite its vital contribution to the social and economic development, the nature of the construction sector which compounded with wide range of unethical issues has called for the urgent needs to promote an ethical business philosophy in line with the concept of corporate social responsibility (CSR). However, the concept of CSR and how it was implemented within the construction sector has yet to be clearly understood. In this paper, focus is given to understand of crucial factors that lead to successful adoption of CSR in practice. Theoretically, this paper could provide a better understanding on how to successfully integrating CSR into business strategies and in turn, maximum benefits from such effort could be expected.